Do Firm Size and Leverage Determine Distance to Corporate Bankruptcy? Evidence from Listed Firms in Kenya - Tarus , John K. (African Journal of Education,Science and Technology (AJEST), 2022)
Over the past decades, corporate bankruptcy has been a major problem both in developed and emerging economies. This is evident by the statistics of corporate bankruptcy rising from year to year. This study aims to investigate the determinants of distance to corporate bankruptcy among listed firms in Kenya. The study was guided by the trade-off theory, normative theory, and explanatory research design was adopted. The target population consisted of 45 listed companies that have continually operated on the Nairobi Securities Exchange for 6 years from 2015 to 2020. The study findings showed that firm size had a positive and significant effect on the distance to corporate bankruptcy (β= 0.281, p<0.05), while leverage had a negative and significant effect on the distance to corporate bankruptcy (β= -0.321, p- <0.05). The study concludes that an increase in firm size leads to corporate bankruptcy, while leverage reduces the distance to corporate bankruptcy. Thus, it would be prudent for firms experiencing a downturn to reduce the scope of their operational output rather than seek financial aid from financial institutions since it can result in bankruptcy. While firms should ensure that debt borrowed realizes a higher return to stockholders so that they can earn more on their assets than the cost of the money used to finance these debts.